ANALISIS KARTOGRAFI KASUS WABAH AFRICAN SWINE FEVER DI KABUPATEN DAIRI PROVINSI SUMATERA UTARA - Roza Azizah Primatika; Bambang Sumiarto; Dyah Ayu Widiasih; Yatri Drastini; Heru Susetya; Widagdo Sri Nugroho; M.Th. Khrisdiana Putri (Jurnal Sain Veteriner, 2023)
African Swine Fever (ASF) is an infectious disease in pigs caused by the African Swine Fever virus (ASFV) with virus species in the Asfarviridae family and Asfivirus genus. African Swine Fever causes economic losses for pig farmers with the number of deaths until 100%. This study aims to determine the distribution of ASF disease directions in Dairi Regency, North Sumatra Province and clusters and outliers in ASF cases in 2019 and 2020. This research method uses cartographic analysis, namely the distribution of directions and clusters and outliers with Moran's Index. Software using ArcGIS 10.5. This study obtained the results that the distribution of ASF disease in Dairi Regency in 2019 had an average center in Siempat Nempu Hulu District with longitude coordinates of 98.265459 and latitude 2.8055450. The distribution of ASF cases in 2019 is in the northwest – southeast region with a rotation of 121.05°. The ASF case in 2020 has a mean center in Lae Parira District with coordinates of longitude 98.3998 and latitude 2.7367. Meanwhile, the distribution of ASF cases in 2020 is northwest – southeast with a rotation of 133.58°. The conclusion of this study can be seen that cases of swine mortality due to ASF virus have a pattern of distribution of ASF disease and ASF case groups in 2019 and 2020.